KAJIAN IMPLEMENTASI OUTBOUND MANAGEMENT TRAINING DALAM UPAYA PENINGKATAN SOFT SKILLS APARATUR SIPIL NEGARA (ASN) DI KOTA PEKANBARU - Yusriadi, Yusriadi (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
One of the training methods that can improve employee soft skills is Outbound Management Training (OMT). Outbound management training is a training program that is generally known as an alternative method of similar training using indoor media. The research was conducted on the State Civil Apparatus (ASN) in Pekanbaru City where in every year before the Covid 19 pandemic, almost most of the ASN in Pekanbaru city through Local Government Organizations (OPD) participated in outbound management training activities. This study uses a qualitative descriptive approach to phenomenology. Descriptive approach can be interpreted as a problem solving procedure that is investigated by describing or describing the state of the subject or object of research (people, institutions and society) at the present time based on the facts that appear and as they are. The results of this study are the correct and effective implementation of outbound management training will be able to improve the soft skills of participants, especially in the aspects of intrapersonal skills and interpersonal skills